Plan de marketing para la empresa comercial carranza, cantón Quevedo, año 2015 - Carranza Rodríguez, Raúl Vicente (2015)
This research was conducted in the canton Quevedo, Los Rios province, Republic of Ecuador, during the second half of 2014. It was considered as a general objective to determine how to design a marketing plan guides the administrative management in the commercial Carranza and as specific objectives: To investigate the situation and study allows to know the internal and external factors in the company, to know if a monitoring and evaluation system aimed at the enforcement of adequate marketing strategies and action plans, identify whether strategic support for analyzing the achievement of the objectives of marketing plans and contingency investigate how the administrative support in the process of implementing the plan, proposing a marketing plan design. They reached the following main conclusions: Commercial Carranza makes no analysis of the internal and external situation (SWOT), has not done any market research and competitive analysis, and has been the subject of technical analysis, and differential positioning with your company. The company has not identified its strengths, weaknesses, threats and opportunities; It not established the vision and objectives of the mission and market. Marketing strategies are the use of market experience and empirically based; not to advertise and promote their products, by any means, so it is not quantified the cost of advertising systems and control have, or contingency plans. Estimates made empirically and are based on market experience. Do not use a contingency plan or have a marketing plan. The main objective of the proposed marketing plan is to place the Carranza trade as one of the....